Occupational Therapy Interventions for Acute Psychiatric Inpatients: A Scoping Review - Hajar Sabour Eghbali MostafaKhan; Fatemeh Hasanati; zahra nobakht (Journal of Rehabilitation Sciences and Research, 2025)
Background: In recent decades, policy changes in many countries have significantly affected the treatment of people with mental illness (MI), particularly in reducing the length of hospitalization in acute psychiatric departments. Occupational therapists, as key mental health professionals, must consider the impact of these shifts in mental health care delivery and focus on evidence-based interventions suited to the acute psychiatric setting. This review aims to examine existing studies to assess the scope and nature of research on occupational therapy interventions for acute psychiatric inpatients through a scoping review. Method: The scoping review followed the PRISMA Extension for Scoping Reviews guidelines. The study comprised three stages: pre-search, search, and post-search, following the scoping review methodology. A structured search was performed using Web of Science, PubMed, and Scopus for items published up to April 5, 2023. Two independent reviewers evaluated the selected literature in two rounds of review. Results: Articles meeting the inclusion criteria (n=13) were incorporated into the analysis. Most publications originated from Japan, followed by the United States and Germany. For the initial days of an acute inpatient stay, especially given the unpredictability of behavior, tolerance, and unstable symptoms, short individual sessions of 20 minutes or less were generally recommended. Treatment sessions in the selected studies typically ranged from three to five days per week, with each session lasting approximately 45 minutes to 2 hours. Flexible, one-on-one intervention structures appeared beneficial in the early hospitalization phase. Four main elements of occupational therapy interventions in acute mental health were identified: individual assessment and intervention, group therapy, and discharge planning. Interventions were compared with control groups who did not participate in these activities, revealing statistically significant Personal and Social Performance Scale improvements. Using weighted blankets in sensory rooms significantly reduced distress and disruptive behaviors. Studies on MetaCognitive Training (MCT), Cognitive Remediation, and Occupational Connections (OC) demonstrated significant differences in outcomes between intervention and control groups. Conclusion: Occupational therapy interventions in acute psychiatric inpatient settings appear effective. Further studies are warranted to develop and refine these intervention methods for acute psychiatric inpatients.